A multi-objective location-inventory model for a fashionable item in a three-level supply chain. (2016) - Bozorgi-Amiri, Ali; Akram, Roshanak; Taleizadeh, Ata Allah; Yousefi-Babadi, Abolghasem
Nowadays, designing a supply chain considering customers' satisfaction is a practical field in supply chain area. In this paper, a multi-objective location-inventory model in a three-echelon supply chain for a perishable product with a fixed lifetime is extended where manufacturers, distributors and customers are the members of the chain. One of the most important factors for supplying perishable products is the availability time for the customers. So, besides the main objective of each chain including minimisation of transportation, inventory, deterioration and shortage costs, another objective as customers' satisfaction related to delivery times should be considered. Here, the optimal lot-sizes, delivery time between factories and distributors so as to choose and locate the best candidate place, and the optimal flows between layers of supply chain are determined. Also, we analyse the decisions of either sending items directly from factories to customers or sending them to the customers through distributors. Moreover, the mixed integer nonlinear model is solved with GAMS and eventually, several numerical examples are presented. The results show that the proposed model is practical in real world problems.